Firms' Moral Hazard in Sickness Absences - René Böheim; Thomas Leoni (Austrian Institute of Economic Research (WIFO), 2011)
Sick workers in many countries receive sick pay during their illness-related absences from the workplace. In several countries, the social security system insures firms against their workers' sickness absences. However, this insurance may create moral hazard problems for firms, leading to the inefficient monitoring of absences or to an underinvestment in their prevention. In the present paper, we investigate firms' moral hazard problems in sickness absences by analysing a legislative change that took place in Austria in 2000. In September 2000, an insurance fund that refunded firms for the costs of their blue-collar workers' sickness absences was abolished (firms did not receive a similar refund for their white-collar workers' sickness absences). Before that time, small firms were fully refunded for the wage costs of blue-collar workers' sickness absences. Large firms, by contrast, were refunded only 70 percent of the wages paid to sick blue-collar workers. Using a difference-in-differences-in-differences approach, we estimate the causal impact of refunding firms for their workers' sickness absences. Our results indicate that the incidences of blue-collar workers' sicknesses dropped by approximately 8 percent and sickness absences were almost 11 percent shorter following the removal of the refund. Several robustness checks confirm these results.
Keywords: 330; Absenteeism Moral Hazard Sickness Insurance; Arbeiter; Fehlzeit; Moral Hazard; Versicherungsschutz; Unternehmen; Österreich